2012
DOI: 10.1016/j.jtcvs.2012.05.053
|View full text |Cite
|
Sign up to set email alerts
|

The “growing teratoma syndrome” in primary mediastinal nonseminomatous germ cell tumors: Criteria based on current practice

Abstract: The growing teratoma syndrome should be defined not only as a growing mediastinal mass but also with secondary cardiopulmonary deterioration precluding safe completion of planned chemotherapy in the presence of declining serum tumor markers. Prompt recognition of this syndrome, discontinuation of chemotherapy, and surgical intervention can result in cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 15 publications
(13 reference statements)
1
43
0
Order By: Relevance
“…For primary mediastinal NSGCT, Kesler et al proposed that the criteria for GTS also include cardiopulmonary deterioration due to compression of vasculature, heart or lungs [14]. GTS has been commonly reported with the BEP chemotherapy regimen as in our patient [1].…”
Section: Discussionmentioning
confidence: 85%
“…For primary mediastinal NSGCT, Kesler et al proposed that the criteria for GTS also include cardiopulmonary deterioration due to compression of vasculature, heart or lungs [14]. GTS has been commonly reported with the BEP chemotherapy regimen as in our patient [1].…”
Section: Discussionmentioning
confidence: 85%
“…In the presence of residual tumor or GTS surgical resection are proposed by most authors. [10][11][12] Sometimes the patient with GTS may refer in a bad condition and urgent operation may be necessary [10]. Sarkaria et al [7] reported good prognostic factors in a series of 43% mixing type of totally 56 NSGCT patients as, R0 surgical resection after standard BEP chemotherapy, postoperative pathology demonstrates necrosis instead of teratoma, descending tumor marker levels after chemotherapy and prior stage I-II.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection of residual disease after chemotherapy shows residual viable tumor in 30-47 % of patients [137,138]. Factors that contribute to inferior survival include an overall poorer response to chemotherapy and higher incidence of degenerative non-germ cell cancer pathology in the residual mass [139]. Age ≥12 years is also suggested as an adverse prognostic factor [77].…”
Section: Outcome Of Mediastinal Germ Cell Tumorsmentioning
confidence: 99%
“…The "growing teratoma syndrome" [139] defines a mediastinal mass that is growing subsequently to neoadjuvant therapy and is associated with secondary cardiopulmonary deterioration precluding safe completion of planned chemotherapy in the presence of declining serum tumor markers. The term was first coined by Logothetis and colleagues [149] who reported patients with non-seminomatous testicular cancer and growing retroperitoneal or lung masses during observation after chemotherapy.…”
Section: Outcome Of Mediastinal Germ Cell Tumorsmentioning
confidence: 99%
See 1 more Smart Citation